2021
DOI: 10.1021/acs.inorgchem.1c00248
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Co2+ Coordination in Cobalt Layered Double Hydroxide Nanosheets via Fe3+ Doping for Efficient Oxygen Evolution

Abstract: Inexpensive and efficient electrocatalysts are crucial for the development and practical application of energy conversion and storage technologies. Layered-double-hydroxide (LDH) materials have attracted much attention due to the special layered structure, but their electrocatalytic activity and stability are still limited. Herein, we propose to tune Co 2+ occupancy and coordination in cobaltbased LDH nanosheets via Fe 3+ doping for efficient and stable electrocatalysis for oxygen evolution reaction (OER). It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…Fe concentration is not a sufficient parameter for catalyst optimization, since the Fe content should be closely adjusted to the morphology and size of the Co oxide host samples in order to achieve an enhancement effect in OER performance. Previously published literature on Fe-doped cobalt oxyhydroxide OER catalysts shows that a plethora of synthesis methods, doping techniques, and resulting structural morphologies can lead to vastly different suggested “optimal” Fe-doping concentrations ranging between 3% and 70% ,, , Some of these studies have discussed the importance of structural features, such as edges and vacancies, on the OER activity, , while others have importantly investigated different synthesis modes to incorporate Fe and shown vast performance changes. A main conclusion of our work is that consideration of the anisotropy of dopant locations provided in our study is necessary to explain the observed dependency on Fe concentrations, and a direct comparison of activities requires reanalyzing OER performance data with the actual particle size of active phase, dopant location, and distribution in mind.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe concentration is not a sufficient parameter for catalyst optimization, since the Fe content should be closely adjusted to the morphology and size of the Co oxide host samples in order to achieve an enhancement effect in OER performance. Previously published literature on Fe-doped cobalt oxyhydroxide OER catalysts shows that a plethora of synthesis methods, doping techniques, and resulting structural morphologies can lead to vastly different suggested “optimal” Fe-doping concentrations ranging between 3% and 70% ,, , Some of these studies have discussed the importance of structural features, such as edges and vacancies, on the OER activity, , while others have importantly investigated different synthesis modes to incorporate Fe and shown vast performance changes. A main conclusion of our work is that consideration of the anisotropy of dopant locations provided in our study is necessary to explain the observed dependency on Fe concentrations, and a direct comparison of activities requires reanalyzing OER performance data with the actual particle size of active phase, dopant location, and distribution in mind.…”
Section: Resultsmentioning
confidence: 99%
“…A set of materials with very prominent catalytic dopant effects are represented by mixed transition metal oxide systems consisting of Fe added to Co or Ni oxides. These materials are considered among the best earth-abundant catalyst candidates to replace the high cost and scarce noble metal-based oxygen evolution reaction (OER) catalysts like Ir and Ru for alkaline conditions. The active form of the mixed oxides is associated with an oxyhydroxide phase (denoted as Co­(Fe)­OOH x and Ni­(Fe)­OOH x ), shown to be present as hexagonal platelet nanoparticles under OER conditions. , According to the literature, the observed OER activity is highly sensitive to the Fe concentration. However, the role of Fe dopants remains debated and an optimal Fe-doping synthesis procedure remains to be developed, exemplified by the wide range of OER activities observed for a given Fe concentration. , Moreover, a wide range of Fe concentrations from 3% to 70% have been reported as an optimal doping level for OER activity. , Extensive characterization efforts have utilized microscopy and spectroscopy techniques and computational modeling for Co­(Fe)­OOH x and Ni­(Fe)­OOH x to investigate the promoting effect of Fe. Several active sites in Fe-containing oxides/(oxy)­hydroxides have been suggested, including the possibility of under-coordinated edge sites involving alternating Fe and Co sites being the best sites for OER. , Atom-resolved scanning tunneling microscopy (STM) imaging and density functional theory (DFT) calculations have, for example, directly shown that hexagonal cobalt oxide nanoparticles on Au(111) exhibit different electrocatalytic activity at the under-coordinated edges of the nanoparticles as compared to the basal planes, in line with edge reactivity reported for exfoliated CoOOH x . , For catalyst systems where Fe has been found to have a promotional effect, it has been proposed that the Fe dopants embedded in the Co oxyhydroxide result in an Fe–O bond shortening and a high oxidation state of Fe, which then has lead authors to conclude that Fe is the active site for OER. , Operando X-ray photoemission and absorption spectroscopies have shed light on the chemical state of Fe dopants, …”
mentioning
confidence: 99%
“…Cationic doping can be regarded as an efficient way to tune the morphology and electronic structure of LDHs, where metal atoms with a higher valence state can act as dopants [ 111 , 112 ]. Recently, Zheng et al proposed that the doping of Fe 3+ into cobalt-based LDH nanosheets can tune the Co 2+ occupancy and coordination [ 113 ]. It was believed that the Fe 3+ dopant can regulate the coordination of Co 2+ in CoO 4 tetrahedra and CoO 6 octahedra.…”
Section: Design Strategies Of Tm-based Ldhs For Improved Oer Catalysismentioning
confidence: 99%
“…Moreover, the intrinsic activity of LDHs can be fine-tuned by adjusting the molar ratio of the metal components. For example, Liu et al [139] found that the molar ratio of Co/Fe greatly affected the OER electrocatalytic performance of CoFe-LDHs by controlling the ratio of CoO 6 octahedrons and CoO 4 tetrahedrons. With increasing Fe content, there were fewer CoO 4 tetrahedra when the ratio reached a certain degree (Co/Fe = 5:1), resulting in higher OER performance than the other with a Co/Fe ratio of 3:1.…”
Section: Regulation Of Layer Compositionmentioning
confidence: 99%